DA3 Using Community Pharmacies to Conduct Outcomes Research - Ungar, WJ (Value in health, 1998)
Studies of effectiveness require that health outcomes be measured in heterogeneous samples of patients. The Pharmacy Medication Monitoring Program (PMMP) is an outcomes research program which uses community pharmacies to recruit study subjects, resulting in a broad sample of patients treated by physicians with diverse practice patterns. Patients are followed prospectively and undergo repeat telephone interviews at specified intervals. The purpose of this workshop is to demonstrate how community pharmacies can be used to perform high quality, prospective outcomes research. The methods for establishing a network of pharmacies, recruiting patients, and obtaining patient informed consent will be described. The procedures for developing telephone questionnaires and for collecting data on a broad range of topics, such as patient demographics, drug utilization and compliance, prescribing patterns, health services utilization, adverse events, quality of life, out‐of‐pocket expenditure and productivity losses will be discussed. Finally, the applications of community pharmacy‐based outcomes research studies will be presented. These include pharmacoeconomic evaluations for formulary registration, drug utilization review for improving therapeutic regimens, developing disease management strategies for optimizing care, patient profiling for investigating utilization and compliance patterns and measuring health outcomes to assess the impact of health policy decisions. This workshop will benefit industrial and academic researchers engaged in prospective pharmacoeconomic assessments, health services evaluations and outcomes research. Individuals interested in outcomes research methodology and the relationship between outcomes research and health policy decision‐making may also benefit from attending.